The “adult inactivity triad” in patients with chronic kidney disease: A review - Zhang, Fan; Yin, Xiaojing; Huang, Liuyan; Zhang, Huachun (Frontiers in Medicine, 2023)
Background The “pediatric inactivity triad” framework consists of three complex, interrelated conditions influencing physical inactivity and associated health risks. Evidence on the beneficial effects of physical activity in adults with chronic kidney disease (CKD) continues to grow, but few studies have explored the complex interactions behind inactivity in this population. Results Based on the “pediatric inactivity triad” framework and prior research, we would like to propose a new concept, the “adult inactivity triad” in CKD, including (1) exercise deficit disorder, (2) sarcopenia, and (3) physical illiteracy. Individuals can shift from “adult inactivity triad” to “adult activity triad” and move at different rates and directions along the arrows in each of the three components. Conclusion This review explores and summarizes previous research on the three main adult inactivity triad components in the chronic kidney disease population.